Accelerated erosion in a watershed in the southeastern region of Brazil - Dorici, Mariana; Costa, Carlos Wilmer; Prado de Moraes, Mayra Cristina; Piga, Fabiola Geovanna; Lorandi, Reinaldo; Lollo, Jose Augusto de [UNESP]; Moschini, Luiz Eduardo (Springer, 2016)
An understanding of erosive processes and the washing away of sediments to watersheds is an essential tool for decision makers planning water resource use. This study assessed the potential for surface runoff due to natural attributes together with land use/land cover to highlight the potential for accelerated erosion in the Araras River Watershed (352.77 km(2)) at a 1: 50,000 scale. The analytic hierarchy process was used with the data provided to combine geoenvironmental attributes (soil, rock, water, relief and land use/land cover) that trigger erosive processes. Just over 51 % of the basin area presented an average potential for surface runoff, while 76.5 % presented a low to average potential for accelerated erosion. Despite this, upstream areas used for water collection for Araras city show a medium to high potential for surface runoff and accelerated erosion, reducing water infiltration and recharge, and resulting in the silting of reservoirs and water quality damage.
Keywords: Geoprocessing; Soil; Water; Degradation; Brazil